Modeling and speed estimation of a faulty 3-phase induction motor by using extended Kalman filter - Jannati, M. (2015)
This paper presents a modeling technique for a faulty 3-phase Induction Motor (3-phase Induction Motor IM under open-phase fault). The developed model has the same structure of equations as the balanced 3-phase model. It is shown that the model can be utilized to estimate the speed of a faulty IM based on an Extended Kalman Filter (EKF) estimation technique, which was developed for a balanced 3-phase IM. Simulation and experimental results are presented to show the validity of the proposed techniques.